Arthropods biodiversity in a landscape mosaic dominated by organic olive groves in Alentejo (Portugal). - Patanita, M.I (2020)
In olive groves, arthropods represent an important part of the biodiversity, where they can provide multiple ecosystem services, such as the biological control of crop pests. This service helps maintaining agricultural productivity and reduces the need of pesticide inputs. The objective of this work was to study the abundance and diversity of arthropods in a landscape mosaic dominated by organic olive groves in Alentejo, Portugal. In total, 7809 specimens were collected, belonging to 10 orders. Diptera was the most abundant ones representing 33.55%, followed by Thysanoptera with 23.83 % and Coleoptera with 20.69%. The abundance of Coccinellidae and Staphylinidae families was higher in the olive groves compared with the holm oak, that could be an indicator of their functions in olive grove agroecosystems.